Assessment and mitigation of biosecurity risks associated with macroalgae inclusion in farmed abalone diets in South Africa - Mwangudza, Petronilla Masika (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
The provision of biosecure diets for use in intensive aquaculture conditions requires attention, to reduce the risk of introducing potential pathogens to the farmed stock. Such introductions could lead to infections and disease outbreaks. Despite the benefits associated with macroalgae inclusion in abalone diets, several microbial hazard cases have been reported in the animal feed and human food industries. This has necessitated the application of biosecurity measures on fresh macroalgae to reduce or eliminate potential hazards and the risks of pathogen transfer to abalone stock when used as a feed or feed supplement. The present thesis assessed the efficacy of different processing treatments, including heat, ultra-violet irradiation (UVC), different pH levels, salinity concentrations, and povo-iodine on the inactivation of potential macroalgaetransmitted abalone pathogens. The effect of the processed macroalgae on the growth, health and gut microbial composition of abalone were also explored and compared with abalone fed non-processed diets. The efficacy of the different processing treatments was initially assessed on pure cultures of the test pathogens, which included a bacterium (Vibrio anguillarum), an oomycete (Halioticida noduliformans) and the bacteriophage lambda. Data from the initial assessments were then used to select the most optimal treatments for further assessment on the test pathogens inoculated in a macroalgae matrix, to simulate a more natural scenario. The viability of the three test pathogens following exposure to different processing treatments was assessed using culture methods. The results indicated that a combination of three treatments; disinfection using povo-iodine solution (5000 mg/L) for 20 min, oven drying 40 â„ƒ for 8.0 h and UVC treatment for 10 min rendered all the test pathogens non-culturable. Growth trials were conducted to assess the effect of the biosecure macroalgae Ecklonia maxima, Ulva lacinulata and Gracilaria gracilis on the growth performance of the abalone Haliotis midae. The macroalgae were subjected to the combination of three biosecurity processing treatments and experimental diets were then formulated to incorporate the macroalgae that had been subjected to the biosecurity processing treatments as well as macroalgae that were not. Growth parameters of the abalone after a 150-day feeding trial were compared between the biosecure and non-bioseeure macroalgae dietary treatments. Overall, the lowest growth was observed in the abalone fed with the control diet (AbfeedTM S34R) compared to all the macroalgae diets. However, no significant differences in abalone weight and shell length were recorded between the dietary treatments after the 150-day growth trial with an overall mean final weight (Â } standard error) of 56.55 Â } 0.78 g and a mean final length of 66.26 Â } 0.344 mm (RM-ANOVA: F(18,63) = 0.706; p = 0.792; : F(18,63) = 0.941; p = 0.535 respectively). Similarly, the biosecurity process method (biosecure vs. non-biosecure) did not have an impact on abalone weights and shell length (p > 0.05). Moreover, specific growth rate, length gain and condition factor of abalone did not differ between the biosecure and nonbiosecure dietary treatments with overall means (Â }standard error) of 0.27 Â } 0.01 % bw/d, 1.79 Â } 0.07 mm/month and 1.13 Â } 0.01, respectively (p > 0.05). Dietary macroalgae are known to contribute to the gut microflora of abalone. To determine if the biosecure process influenced this community complex, a next generation sequencing (NGS) approach was used to identify and compare the bacterial communities in abalone that were fed diets containing macroalgae that had been subjected to biosecurity treatment and those that were not. The NGS approach was also used to determine the gut microbiome profile of the abalone fed with a formulated diet supplemented with fresh U. lacinulata and G. gracilis to assess the potential modulatory effect seaweeds and their associated microbiota may have on the gut microbiome of H. midae. The bacterial alpha diversity did not differ significantly across all the diets at family, genus and species levels (p > 0.05). No significant differences in the microbiome composition were detected indicating little or no dissimilarities of the bacterial communities between the diets for all the biosecure and non-biosecure macroalgae diets. A similar core microbiome was also observed in the digestive tracts of abalone fed with the biosecure and non-biosecure diets. It was concluded that the biosecure process did not influence the natural microbiota of abalone that were fed dietary ingredients that were subjected to the process. The findings of this research have contributed to understanding the production of biosecure macroalgae formulated diets without compromising their benefits to the growth and health of farmed abalone. The combined treatment used in this study can be applied in the macroalgae and the feed industry to produce biosecure feeds.
Keywords: Biosecurity; Seaweed; Abalone culture -- South Africa; Abalones Feeding and feeds; Haliotis midae; High-throughput nucleotide sequencing